2023
DOI: 10.3390/jpm13040618
|View full text |Cite
|
Sign up to set email alerts
|

Care for Patients with Type-2 Chronic Rhinosinusitis

Abstract: In the last 20 years, growing interest in chronic rhinosinusitis (CRS) has become evident in medical literature; nevertheless, it is still difficult to identify the real prevalence of the disease. Epidemiological studies are few and focused on heterogeneous populations and diagnostic methods. Recent research has contributed to identifying CRS as a disease characterized by heterogeneous clinical scenarios, high impact on quality of life, and elevated social costs. Patient stratification with phenotypes and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…These results confirm that the endoscopic and symptomatological differences may further turn into divergences from a psychiatric point of view, in terms of depression and anxiety. According to our evidence, we want to stress the need for a change from a “disease” to a “patient-centered” medicine, in order to improve the whole healthcare process from a holistic perspective [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm that the endoscopic and symptomatological differences may further turn into divergences from a psychiatric point of view, in terms of depression and anxiety. According to our evidence, we want to stress the need for a change from a “disease” to a “patient-centered” medicine, in order to improve the whole healthcare process from a holistic perspective [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, it is recommended to assemble a multidisciplinary team comprising, at the very least, otolaryngologists, allergologists/clinical immunologists, pneumologists, and psychologists. This collaborative approach aims to provide the most effective diagnostic and therapeutic strategies for the patient, especially in an era where emerging therapeutic interventions, such as biologic agents, are shaping the landscape of managing type-2 related disorders of the airways [78].…”
Section: A Systemic Conditionmentioning
confidence: 99%
“…[1][2][3][4] The clinical presentation of CRSwNP typically includes nasal congestion, rhinorrhea, facial pressure or pain, and hyposmia for 12 weeks or more. 5 While the overall burden has been reported to be comparable with other chronic diseases such as diabetes, COPD, and asthma, there are still some blind spots in the full understanding of the clinical traits of this condition. 6 The pathophysiology of CRSwNP is yet to be completely clarified, but it has been shown that its symptoms are associated with both local and systemic inflammatory processes, which may cause topical therapies to fail in permanently controlling the disease.…”
Section: Introductionmentioning
confidence: 99%